Analisis Pengelolaan APBDes Dalam Penanganan Darurat Bencana Erupsi Gunung Lewotobi (Studi Kasus Pada Pemerintahan Desa Boru) - Kristina Ago Lewar; Konstantinus Pati Sanga; Petrus Da Silva (Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine how the Village Revenue and Expenditure Budget was managed in handling emergency caused by the vilcanic eruption in Boru Village, Wulanggitang Sub-district, East Flores Regency. The Lewotobi volcano eruption disaster that occurred at the end of December 2023 required the vullage government to make quick and appropriate budget adjustments. This research used a qualitative approach with the Miles and Huberman analysis method, which included data reduction, data presentation, and conclusion drawing. Data collection techniques were carried out through interviews, documentation, and observation. The results of the research showed that the Village Revenue and Expenditure Budget planning was carried out adaptively through a Spesial Village Meeting. The implementation of emergency funds was effective despite communication constraints, and administration and reporting were still carried out despite delays. The village government had formally accounted for its actions to the regional government and strove to build transparency with the community. This research supported the stewadship theory, in which village governments acted as trustees of the community in managing public finances. This research was also in line with several previous studies that emphasize the importance of accountability and participation in village fund management, especially in crisis situations.